Evaluation of Raktadushti in Madatyaya Vyadhi: A Cross Sectional Observational Study: LifeScience-Ayurveda - M. Pande, Sumant; D Joshi, Maheshwari; H Thakare, Seema (International Journal of Life Science and Pharma Research, 2023)
All over the world, alcohol consumption is becoming a lifestyle. The fashion of alcohol ingestion leads to habits of chronicalcoholism. Alcoholism (Madyapaan) is a behavioral disorder characterized by repetitive and excessive consumption of alcohol (Madya). It isobserved that long-term consumption of alcohol damages the liver to a very large extent, leading to either Alcoholic liver disease or livercirrhosis. In Ayurveda, this condition can be correlated with ’Madatyaya.’ Madya is described as the main etiological factor of various diseasesat multiple places in Ayurvedic classics, but madatyaya is a primary one. Ayurved explains the etiology, pathogenesis, and treatment ofmadatyaya, but the specific srotodushti is not explained. When characteristics of madya and causative moolasthanavikruti (Hepatotoxicity) areconsidered, it is assumed that madya may cause raktadushti also. Hence this topic is an attempt to evaluate raktadushti in madatyaya vyadhi. Itis a cross-sectional observational study performed on 50 patients of Madatyaya. Patients were examined thoroughly, and all the details werenoted in a specially designed case record format. A comparative study of madatyaya and raktadushti was conducted; also assessment ofraktadushti was done based on symptoms of raktadushti observed in those patients. Collected data and the observations are then analyzed bystatistical tests such as the chi-square test and correlation regression. This study proves the positive correlation between madyatyaya andraktadushti. It may be the alcohol metabolized primarily in the liver, which is getting damaged by long-term consumption. Ayurveda explainsYakrita and pleeha as the moolasthana (roots) of Raktavaha srotas. This moolasthana dushti (damage to the root) causes damage to the wholesystem (Raktavaha srotas); hence madatyaya vyadhi can be labeled as a disease of Raktavaha srotas.